PENGUJIAN SUHU DAN KELEMBAPAN PADA ALAT PENGERING GABAH MENGGUNANAKAN SENSOR DHT11 - Alfith Alfith; Asnal Effendi; Aswir Premadi; Yogi Saputra (Ensiklopedia of Journal, 2022)
Many kinds of sensors for measuring temperature or humidity, such as LM35, DS18S20 and DHT11. To measure temperature and humidity in mushrooms, you can choose the DHT11 sensor. The DHT11 has a calibrated digital output. This sensor consists of a resistive type humidity measuring component and temperature measurement via NTC and is connected to 8 bits, so that it gives quite good results, sufficient response speed, has good resistance to interference. The interface used is a single write serial interface which is quite fast and easy. The sensor size is small, the need for low power consumption and is able to transmit its output within a distance of 20 meters. The DHT11 sensor can be used for measuring room temperature, measuring incubator temperature and humidity and others. If the sensor distance is less than 20 meters, it is necessary to install a 5KΩ pull-up resistor on the data pin. Meanwhile, if the distance is more than 20 meters, it is necessary to adjust the size of the pull up resistor. The power supply required for this DHT11 ranges from 3.5V to 5V. Access to the sensor is only allowed more than 1 second after the first power supply is provided.